1996
DOI: 10.1113/expphysiol.1996.sp003994
|View full text |Cite
|
Sign up to set email alerts
|

Non‐adrenergic, non‐cholinergic influences on parotid acinar degranulation in response to stimulation of the parasympathetic innervation in the anaesthetized rat

Abstract: SUMMARYIn pentobarbitione-anaesthetized rats the parasympathetic auriculotemporal nerve of the parotid gland was continuously stimulated at supramaximal voltage and at maximal frequency (40 Hz) for salivary secretion. The animals were pretreated with phentolamine and propranolol (2 mg kg-' I.P.of each) and, in some groups, additionally with atropine (2 mg kg-1 i.p.). Morphometric assessment at the light microscopic level (x 100) showed that the numerical density of parotid acinar secretory granules (per 100 l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Ekström 1987Ekström , 2001Ekström and Ekström 2001;Ekström et al 1993Ekström et al , 1996Ekström et al , 1998 have shown that saliva secretion may also be elicited by a variety of secretory neuropeptides housed in stromal nerve terminals. The residual stimulation still elicited in our experiments with Cloz after treatment with both muscarinic (A) and adrenergic (Phe and Pro) antagonists may be attributable to its action on receptors located on intraglandular nerve terminals causing the exocytosis of peptidic neurotransmitters in so-called non-adrenergic/noncholinergic (NANC) transmission (Ekström et al 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Ekström 1987Ekström , 2001Ekström and Ekström 2001;Ekström et al 1993Ekström et al , 1996Ekström et al , 1998 have shown that saliva secretion may also be elicited by a variety of secretory neuropeptides housed in stromal nerve terminals. The residual stimulation still elicited in our experiments with Cloz after treatment with both muscarinic (A) and adrenergic (Phe and Pro) antagonists may be attributable to its action on receptors located on intraglandular nerve terminals causing the exocytosis of peptidic neurotransmitters in so-called non-adrenergic/noncholinergic (NANC) transmission (Ekström et al 1998).…”
Section: Discussionmentioning
confidence: 97%
“…the co-transmitter of acetylcholine, vasoactive intestinal peptide, evoke exocytosis, demonstrating a regulatory role in this process for parasympathetic transmitters in both animals (Ekstr€ om et al 1994;Ekstr€ om & Ekstr€ om, 2001;Ekstr€ om, 2002) and humans (Del Fiacco et al 2015). In agreement with the exocytotic responses to autonomimetics, animal experiments show varying degrees of acinar granule depletion in response to the electrical stimulation of the sympathetic and parasympathetic innervations (Garrett & Thulin, 1975;Ekstr€ om et al 1994Ekstr€ om et al , 1996. Moreover, hormones, including melatonin, of particular interest in the present context, have been shown to cause the secretion of protein/amylase (C ßevik Aras & Ekstr€ om, 2008) and to evoke exocytosis in salivary glands (Loy et al 2012(Loy et al , 2015; luzindole, an MT1/MT2 antagonist with greater affinity for MT2 receptors (Radio et al 2006), abolished these secretory events evoked by melatonin.…”
Section: Discussionmentioning
confidence: 67%
“…However, the output of protein/amylase decreases markedly and the gland loses its secretory granules [1,2]. The rat parotid saliva contains hundreds of proteins/peptides as shown by high resolution 2-D electrophoresis [3].…”
Section: Introductionmentioning
confidence: 99%